Controlled-Release Fertilizers for Florida Citrus Production - Tom Obreza; Bob Rouse (EDIS, 2004)
In the new age of Florida citrus production, Best Management Practices to protect water quality are being considered across the state. Growers have been encouraged to carefully consider nitrogen (N) fertilizer rates, application schedules, and irrigation management in their groves. Nitrogen sources have received little attention because most managers are accustomed to using water-soluble fertilizers like ammonium nitrate, ammonium sulfate, and urea. Synthetic controlled-release fertilizers (CRFs) have existed commercially for more than 35 years, but other than use in young-tree fertilizer blends, Florida citrus growers have avoided them due to high cost and lack of production experience. This document is SL-214, a fact sheet of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2004.